OP0187 DETERMINING OPTIMAL COOLING AND ADMINISTRATION METHODS FOR CNTX-4975 INTRA-ARTICULAR INJECTION IN SUBJECTS WITH MODERATE TO SEVERE OSTEOARTHRITIS KNEE PAIN. (2nd June 2020) - Stevens, R.; Hanson, P.; Tiseo, P.; Guedes, K.; Campbell, J.; Connolly, J.; Ruggiero, S.; Corliss, M.; Smith, V.; Conaghan, P. G.
Abstract : Background: CNTX-4975 is a highly purified, synthetic capsaicin being developed to provide long-term analgesia after a single intra-articular (IA) injection for patients with moderate to severe osteoarthritis (OA) knee pain. CNTX-4975 IA administration is associated with short-term post-procedural pain that can be attenuated with preemptive joint cooling. Objectives: To evaluate cooling and administration procedures for CNTX-4975 IA injection, with goals of balancing patient comfort and ease of use and assessing clinical response 8 weeks after injection. Methods: This phase 3, open-label, 8-week study (NCT03661996 ) enrolled subjects aged 40–95 y with Kellgren-Lawrence grade 1–4, BMI ≤45 kg/m2, and stable, moderate to severe OA knee pain and who failed ≥2 therapies. Subjects were assigned to unilateral/bilateral CNTX-4975 1 mg IA injections as determined by OA pain/joint replacement status, then randomized by study site to 1 of 5 treatment regimens (Figure). The primary outcome measure assessed Breg cooling control vs other cooling regimens on day 1 using a combined sum of 1) pain (0, none; 4, severe) 30 minutes after CNTX-4975 injection; 2) subject satisfaction (SS) with cooling/injection procedures; and 3) investigator satisfaction (IS) with procedures. SS and IS were measured on a 1–7 scale (1, completely dissatisfied; 7, completely satisfied); pain was reverse scored and normalized (1, severe; 7, none) for equal weighting. Geometric mean ratios (GMR) with 95% CIs were constructed for each regimen vs Breg control (ANCOVA); lower 95% CI >0.7 was considered clinically acceptable. Secondary endpoints included percentage of subjects by subject type meeting criteria for Outcome Measures in Rheumatology-Osteoarthritis Research Society International (OMERACT-OARSI) responders 8 weeks after injection. Safety assessments included TEAEs. Results: The intent-to-treat population included 848 subjects. The primary combined outcome showed that all cooling and administration regimens were clinically acceptable, with the evaluated cold gel wraps being at least as effective as the Breg circulating ice-water wrap (Table). For subjects with unilateral OA, OMERACT-OARSI response rates were 67% in those with no/mild nonindex knee pain and 81% in those with nonindex knee single joint replacement. For subjects with bilateral knee OA receiving bilateral injections, response rates for index and nonindex knees were 73% and 79%. TEAEs were reported in 22% of subjects; <1% were serious. TEAEs occurring in >2% of subjects were procedural pain (2.9%), arthralgia (2.2%), and nausea (2.1%), with no meaningful differences across groups. Conclusion: All cooling regimens for CNTX-4975 IA administration were clinically acceptable and well tolerated, offering feasible options for use in routine practice. Importantly, high levels of clinical response were observed 8 weeks after unilateral or bilateral knee injections for moderate to severe OA knee pain. Primary Combined Endpoint Outcome in the Index Knee, Normalized Scale, by Cooling and Administration Procedure (ANCOVA Model) Disclosure of Interests: Randall Stevens Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, Peter Hanson Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, Paul Tiseo Employee of: Centrexion Therapeutics Corp, Kimberly Guedes Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, James Campbell Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, James Connolly Employee of: Centrexion Therapeutics Corp, Stephanie Ruggiero Employee of: Centrexion Therapeutics Corp, Meg Corliss Employee of: Centrexion Therapeutics Corp, Valerie Smith Consultant of: Centrexion Therapeutics Corp, Philip G Conaghan Consultant of: AbbVie, BMS, Eli Lilly, EMD Serono, Flexion Therapeutics, Galapagos, GSK, Novartis, Pfizer, Speakers bureau: AbbVie, Eli Lilly, Novartis, Pfizer